Nikah Beda Agama dan Dampaknya Terhadap Psikologi Anak Perspektif Maqashid al-Syari’ah - Saini, Saini (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
This research explores the psychological impact of interfaith marriages on children in the Tapal Kuda area of East Java. Children from interfaith marriages only have multicultural awareness. However, it also has an impact on children's psychology. In this context, children often feel trapped between two different belief systems resulting from interfaith marriages, which can cause confusion and stress. Different beliefs and beliefs give children choices, which, of course, make children psychologically stressed by following one of them's beliefs. Pressure to choose one religion over another or to meet the expectations of both parents can cause significant internal conflict. This study uses a qualitative approach with case studies. The results show that these children show strong multicultural awareness but also experience significant challenges related to religious identity and mental health. Social pressure and confusion regarding religious identity often trigger their emotional instability, leading to feelings of anxiety, stress, and lack of self-confidence, ultimately affecting their mental health. Therefore, an inclusive approach is needed from families, communities, and educational institutions to support their mental health. This view is consistent with the principles of Maqashid al-Syari’ah, especially regarding protecting one's nasab (hifz an-nasl), protecting the soul (hifz al-nafs), and protecting religion (hifz al-din).